Differences in Condom Use among Never Married Young Men and Women in Zambia - Phillimon Ndubani; Thankian Kusanthan (Archives of Current Research International, 2018)
The present study explored factors that affect the use of condoms among young men and women who have never been married in Zambia. The data that was employed in this study was derived from the 2013 Zambia Demographic Health Survey (ZDHS). Logistic regression analysis was used to identify factors affecting gender differentials in condom usage by considering socio-economic variables. The study revealed that about 12 per cent of females and 16 per cent of males reported having had sex with more than one to three partners; and 29 per cent of females and 37 per cent of males reported using condoms during their last sex intercourse with their partners. Strong predictors of condom usage were Age, Wealth status, Educational level, Media exposure and alcohol drinking. The study findings showed that females who had completed secondary education were 1.4 times more likely to report having used condoms during sexual intercourse with their partners. Male youths who were working were 1.5 times more likely to report having used a condom during their last sexual intercourse with their partners compared to the male youths who were not working. It was further revealed that, the socio-economic and demographic factors were cardinal determinants of condom use among youths who have never been married youths in Zambia. These findings have shown consistency with other studies done within sub-Saharan Africa and other countries in relation to the determinants of condom use among youths who have never been married. The study recommends interventions to promote and encourage condom useby taking into account the gender differentials of age, media exposure and socioeconomic status of the target populations.